Smart trash system / Nurul Amira Bamran...[et al.] - Bamran, Nurul Amira; Zainalarifin, Siti Nur Izaty; Abu Hassan, Nur Ain Natasya; Husin, Nur Amni Mustaqimah; Norzaiwin, Nurin Hidayah (2019)
Ratu Engineering Sdn.Bhd is a company that brings smart solutions to life. High tech companies developing, manufacturing and serving customers with smart solutions in industries that focused on sustainability which provide a cleantech products providing automatic waste collection and sorting solutions. The product of this company is a high-tech waste collection machine name 'Smart Trash System'. It gives customers all the pneumatic waste collections benefits with low cost: less odours, no overfilled waste bins, emission reduction and free design of the residential block with safety and pleasantness in mind. The Smart Trash System has two parts of machine which is The Waste Collection Cyclones and Waste Collection Points. The Waste Collection Cyclones can be placed far from the residential home, but the Waste Collection Points are close. It is convenient and safe for the residents.